EVALUATION OF MINIMUM COMPETENCY ASSESSMENT (AKM) IN CLASS VIII STUDENTS AT PERTAMAN MIDDLE SCHOOL (SMP) ON THE LITERACY AND NUMERATION ABILITIES OF STUDENTS IN THE BOYOLALI REGION - avika, azizah (Melekliterasi Press, 2025)
One of the work programs that must be carried out by class VI teaching campus participants is to carry out the Minimum Competency Assessment (AKM) for Elementary School (SD) level, carried out in class V, at Junior High School (SMP) level, carried out in class VIII and for Vocational High Schools ( SMK) is carried out in class XI. In this activity we carried out a Minimum Competency Assessment (AKM) at the Junior High School (SMP) level. This activity was carried out to determine the extent of students' literacy and numeracy abilities. Minimum Competency Assessment (AKM) is carried out in two stages, namely pre-test and post-test. In the pre-test, 35% of students answered correctly in numeracy and 50% in literacy. In the post test, 32% of students answered correctly in numeracy and literacy. So the Minimum Competency Assessment (AKM) program is running quite well. From the results obtained, the results of the Minimum Competency Assessment (AKM) literacy increased and the results of the Minimum Competency Assessment (AKM) decreased.